Heart rate variability and depressive symptoms: a cross-lagged analysis over a 10-year period in the Whitehall II study - Jandackova, V K; Britton, A; Malik, M; Steptoe, A (Psychological medicine, 2016)
BACKGROUND: People with depression tend to have lower heart rate variability (HRV), but the temporal sequence is poorly understood. In a sample of the general population, we prospectively examined whether HRV measures predict subsequent depressive symptoms or whether depressive symptoms predict subsequent levels of HRV. METHOD: Data from the fifth (1997-1999) and ninth (2007-2009) phases of the UK Whitehall II longitudinal population-based cohort study were analysed with an average follow-up of 10.5 years. The sample size for the prospective analysis depended on the analysis and ranged from 2334 (644 women) to 2276 (602 women). HRV measures during 5 min of supine rest were obtained. Depressive symptoms were evaluated by four cognitive symptoms of depression from the General Health Questionnaire. RESULTS: At follow-up assessment, depressive symptoms were inversely associated with HRV measures independently of antidepressant medication use in men but not in women. Prospectively, lower baseline heart rate and higher HRV measures were associated with a lower likelihood of incident depressive symptoms at follow-up in men without depressive symptoms at baseline. Similar but statistically insignificant associations were found in women. Adjustments for known confounders including sociodemographic and lifestyle factors, cardiometabolic conditions or medication did not change the predictive effect of HRV on incident depressive symptoms at follow-up. Depressive symptoms at baseline were not associated with heart rate or HRV at follow-up in either sex. CONCLUSIONS: These findings are consistent with an aetiological role of the autonomic nervous system in depression onset.
Keywords: Humans; Sex Factors; lidé; longitudinální studie; Longitudinal Studies; deprese; Female; lidé středního věku; Depression; Male; Heart Rate; Adult; London; dospělí; sexuální faktory; srdeční frekvence; Londýn; Middle Aged; ženské pohlaví; mužské pohlaví